IMPLEMENTASI TERAPI KOMPLEMENTER DALAM PELAYANAN KEBIDAAN DI KLINIK PRATAMA SALBIYANA MEDAN - HALIMAH, Halimatussakdiyah Lubis; Fika Lestari; Yusnaini (Amal Insani Foundation, 2023)
Complementary therapies are a group of different medical and healthcare systems, practices, and products that are not generally part of conventional medicine. The role of the midwife as a promotive, preventive agent for health is required to be responsive and innovative in dealing with situations. Professionalism in handling is highly demanded in dealing with problems during pregnancy. midwives are authorized to monitor the growth and development of infants through early detection and stimulation of growth and development. One form of stimulation that has been carried out by the community is massage. Complementary midwifery care that can be implemented for pregnant women includes pregnancy birth ball exercises, baby massage, or baby massage. This community service will be held at the Pratama Salbiyana Clinic in Medan from 15 January to 16 February 2023 at the Pratama Salbiyana Clinic in Medan, Jalan Kebun Sayur Raya Pasar 9 Dusun 6a, Manunggal Village, Labuhan Deli District, Arah Marelan. Participants in this community service activity are midwives, pregnant women, and mothers with babies aged 2-6 months.